1990
DOI: 10.1136/gut.31.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal and gastric motor activity in patients with bulimia nervosa.

Abstract: Previous studies showed that symptoms of oesophageal motor disorders can be misinterpreted as indicating anorexia nervosa and that in primary anorexia nervosa gastric motility is frequently impaired. We investigated in 32 women with bulimia nervosa whether symptoms of oesophageal motor disorders could be obscured by or be mistaken as forming part of bulimic behaviour, and whether impaired gastric motility was frequent as well. Oesophageal motility was normal in 18 of26 patients studied, another four had incomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…In this respect, kl/kl mice develop generalized intestinal neuromuscular hypoplasia, secondary to a reduction in smooth muscle myosin [40]. Similarly, patients with AN may suffer from abnormal gastrointestinal motility, likely leading to gastrointestinal symptoms such as dyspepsia and constipation that may, in turn, further discourage eating [41].…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, kl/kl mice develop generalized intestinal neuromuscular hypoplasia, secondary to a reduction in smooth muscle myosin [40]. Similarly, patients with AN may suffer from abnormal gastrointestinal motility, likely leading to gastrointestinal symptoms such as dyspepsia and constipation that may, in turn, further discourage eating [41].…”
Section: Discussionmentioning
confidence: 97%
“…Often, several years elapse before the disease is diagnosed, and, during this time, other symptoms, such as vomiting and weight loss, are common [3]. During this period, achalasia can be mistaken for anorexia nervosa or bulimia nervosa, although reports of achalasia in adults and adolescents misdiagnosed as eating disorder exist in the literature [1,[3][4][5][6][7][8][9][10][11][12][13]. Differential diagnosis between achalasia and eating disorders is not always obvious.…”
Section: Discussionmentioning
confidence: 98%
“…During the follow-up of eating disorders, changes in the symptoms' frequency, severity and characteristics may be clues to a differential diagnosis and the onset of new complications. 13,14 In the literature, a study reported that the rate of achalasia was elevated among patients with BN compared to the general population, 7 and there are some case reports about BN patients developing achalasia because of myenteric plexus damage. 13,14 In the present case, although response was achieved through psychological support, the sudden onset of the aggravation of symptoms along with involuntary vomiting, heartburning and pain, which was not previously experienced, prompted referral to a paediatric gastroenterology department, and the presence of achalasia was revealed.…”
Section: Discussionmentioning
confidence: 99%